2009
DOI: 10.1007/s00265-009-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

“Friendships” between new mothers and adult males: adaptive benefits and determinants in wild baboons (Papio cynocephalus)

Abstract: Close associations between adult males and lactating females and their dependent infants are not commonly described in non-monogamous mammals. However, such associations [sometimes called “friendships” (Smuts 1985)] are regularly observed in several primate species in which females mate with multiple males during the fertile period. The absence of mating exclusivity among “friends” suggests that males should invest little in infant care, raising questions about the adaptive significance of friendship bonds. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 85 publications
(116 reference statements)
3
126
2
Order By: Relevance
“…Here, we found that higher female social connectedness to males was predicted by higher female dominance rank. This result suggests that male baboons are a limited, monopolizable resource for females, and females who effectively compete for access to males may experience higher survival, as well as reproductive benefits [38,41,50]. However, in our data, we did not observe a direct effect of female rank on survival.…”
Section: (B) Social and Demographic Predictors Of Social Connectednesscontrasting
confidence: 86%
See 1 more Smart Citation
“…Here, we found that higher female social connectedness to males was predicted by higher female dominance rank. This result suggests that male baboons are a limited, monopolizable resource for females, and females who effectively compete for access to males may experience higher survival, as well as reproductive benefits [38,41,50]. However, in our data, we did not observe a direct effect of female rank on survival.…”
Section: (B) Social and Demographic Predictors Of Social Connectednesscontrasting
confidence: 86%
“…Second, many primate species exhibit close social relationships among adult males and females (sometimes called 'friendships') [27][28][29][30][31][32][33][34][35][36][37]. While the primary benefits of such friendships are thought to be reproductive, including bi-parental offspring care and access to potential mates [28,36,[38][39][40][41][42][43][44][45][46][47][48][49], heterosexual friendships may also benefit females directly via reduced harassment, reduced predation risk or stress mitigation [38,39,[50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Taub 1980). In some baboon species, these preferences may reflect likelihood of paternity to some extent (Nguyen et al 2009;Moscovice et al 2010). In macaques male preferences for infants appear mostly unrelated either to paternity or to past mating (Paul et al 1992;Ménard et al 2001; but see Ménard et al 1992 andOstner et al 2013) but may reflect the male's social relationships with the mother and may be predictive of future mating opportunities (Ménard et al 2001; see also Smuts and Gubernick 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, grooming has been interpreted as a tactic used, usually but not exclusively by females, to gain access to an infant Smuts [1985] (olive), Swedell [2006] (hamadryas), Nguyen et al [2009] (yellow), Huchard et al [2010] (chacma) and this study (Kinda). [Nicolson, 1987;Henzi and Barrett, 2002].…”
Section: Discussionmentioning
confidence: 99%